The Effect of Educator Interaction with Students in Increasing Learning Motivation - Khosyatullah, Zulqi; Nurihsan, Ahmad Juntika; Robandi, Babang (International Conference on Elementary Education, 2021)
This research motivated by the low learning motivation of students and how educators interact with students. This study aims to increase the learning motivation of students with good and correct educator interactions, utilizing short strength, and methods of educators owned. This research is useful for both educators and students because it can be felt directly by students in learning using educator interactions. In terms of interaction, it can be said to be very good an important role in human interaction, where a good interaction can make a complete human role in terms of relationships and human needs. Interactions can meet emotional needs and affect mental health and services dyne. In this case, humans can learn to interpret the meaning of happiness, love, affection, respect, and even hatred and envy. From communicating humans, we can make a role and a human process that always develops with the man the other. In terms of interaction, it can be said that it plays an important role in terms of human interaction, where a good interaction can make a complete human role in terms of relationships and human needs. Interaction can fill needs emotional god and affects mental health and his body. In this case, humans can learn to interpret the meaning of happiness, love, affection, respect, and even hatred and envy. From communicating humans, it can make a springe and human processes that always develop with other humans.